Analisis Sistem Otomasi Perpustakaan Berbasis (SLiMS) Di Perpustakaan SMPN Satu Atap 01 Way Serdang Kabupaten Mesuji - Aldio Ramadlan; Reza Nawafella Alya Parangu; Rahmat Iqbal (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This study aims to analyze the implementation of the Senayan Library Management System (SLiMS) 9 Bulian as a library automation system at the SMPN Satu Atap 01 Way Serdang Library, Mesuji Regency. The background of this research is based on the suboptimal utilization of SLiMS in supporting library management and services, particularly related to human resource readiness and the use of system features. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving the head librarian and library staff. The data analysis focused on perceived ease of use, perceived usefulness, and attitude toward technology usage based on the Technology Acceptance Model (TAM). The results indicate that SLiMS facilitates collection management, membership administration, and circulation services, thereby improving the effectiveness and efficiency of librarians’ work. However, the implementation of SLiMS has not been fully optimized due to limited supporting facilities and insufficient technical competence in utilizing all system features. This study concludes that SLiMS has significant potential to enhance the quality of school library services if supported by continuous training and adequate institutional support.